Mantle cell lymphoma presenting as acute appendicitis. (2015) - Chae, Max; Kumar, Sampath; Cheema, Muhammad
Highlights: Mantle cell lymphoma is an extremely rare form of lymphoma associated with appendicitis. This is one of few reported cases of mantle cell lymphoma showing obstruction of appendiceal lumen. Appendicitis associated with mantle cell lymphoma in this incident is unaffected by the effect of chemotherapy treatments. Abstract: INTRODUCTION: Most cases of appendicitis associated with lymphoma reported in literature are in patients with Burkitt's or large B-cell lymphoma. Mantle cell lymphoma only makes up 4% of all lymphoma cases in the U.S. We report a case of a patient with mantle cell lymphoma presenting with acute appendicitis. PRESENTATION OF CASE: A 75 year old male with a history of left cervical lymphadenopathy biopsied to be mantle cell lymphoma presented with right lower abdomen pain for 3 days. An outpatient CT scan revealed acute appendicitis. Laparoscopic appendectomy was performed without any complication. The histologic examination showed mantle cell lymphoma occluding the lumen of appendix. DISCUSSION: Typically, appendicitis is caused by obstruction of the lumen of appendix by fecalith or lymphoma. A previously reported case of a patient with mantle cell lymphoma who developed appendicitis received chemotherapy before appendectomy. The author could not determine how mantle cell lymphoma contributed to appendicitis because the lumen of appendix was not occluded by the lymphoma, likely from cytoreduction from chemotherapy. We have a patient with mantle cell lymphoma before the patient received chemotherapy who presented with appendicitis. The appendiceal specimen shows the lumen filled with mantle cell lymphoma. CONCLUSION: This is a rare case of mantle cell lymphoma causing obstruction of appendiceal lumen and subsequently appendicitis, unaffected by chemotherapy.